Comparison of analgesic efficacy between TAP block and local site infiltration post operatively in caesarean section - Das, Nabanita; Shukla, Usha; Singh, Dheer; Yadav, Urvashi (International Journal of Research in Medical Sciences, 2018)
Background: Patients undergoing caesarean section need to be alert, comfortable and mobile in order to take care of their babies, for which they must be pain free in post operative period. The aim of present study is to compare the analgesic efficacy of TAP block with local anaesthetic infiltration specifically in LSCS patients in reducing patient pain postoperatively, as well as to decrease the analgesic requirements. Methods: The study population consisted of 60 patients posted for elective and emergency caesarean section. They were blindly divided into two groups of 30 patients each. Group T received 40ml 0.25% Ropivacaine in Transverses abdominis plane (TAP) block for postoperative analgesia and group I received 40ml 0.25% ropivacaine as infiltration at incision site for postoperative analgesia. Patients were observed for numeric pain score NPS, analgesic requirements, total analgesic consumption and adverse effects if any. Results: There was highly significant difference in numeric pain scores at 2nd, 6th, 12th and 24th hours (p<0.0001). Both the time for first rescue analgesic and total amount of analgesic consumed are statistically significant (p<0.0001). Conclusions: TAP block is an effective postoperative analgesic procedure for post caesarean section patients.